Transcriptomic and protein expression analyses of skeletal muscles isolated from Ts1cje mouse model for Down syndrome - Leong, Melody Pui Yee (2017)
Down Syndrome (DS) is caused by an additional copy of human chromosome 21 (HSA21). It is characterised by several clinical phenotypes such as intellectual disability, facial features, early onset dementia, weak immune system and hypotonia. Deficits in motor functions happens throughout development among DS individuals leading to muscle weakness, joint hyperextensibility, delayed acquisition of postural control and poor balance. To date, the underlying cause of hypotonia in DS individuals remains unknown and limited studies on the pathophysiological and molecular characterisation of hypotonia in DS could be found. Ts1Cje is a DS mouse model with partial trisomy of mouse chromosome 16 (MMU16), which encompasses a high number of HSA21 orthologous genes. This mouse model has been well reported to exhibit various typical neuropathological features as well characterised with muscle weakness that is similar to individuals with DS. The hypothesis of this study is that the trisomic genes in MMU16 are over-expressed in Ts1Cje mice and disrupts the functional molecular networks, leading to muscle weakness in Ts1Cje. To test this hypothesis, the study was divided into two major parts namely the targeted approach to study selected important markers in muscle development and function, and global transcriptomic gene expression study to identify novel genes involved in Ts1Cje muscle weakness. In this study, the soleus and extensor digitorum longus (EDL) skeletal muscles were harvested from both Ts1Cje mice and disomic control mice. Reverse transcription quantitative real time polymerase chain reaction (RT-qPCR) analysis of nine selected genes Lamc1, Leprel1, Myl6b, Msn, Pgm5, Tmod1, Istn1, Synj1 and Rcan1 showed an upregulation of the triplicated genes Itsn1, Synj1 and Rcan1 in both soleus and EDL muscles of the Ts1Cje mice. The disomic genes Lamc1, Leprel1, Msn, Pgm5 and Tmod1 did not show any significant dysregulation in expression while Myl6b was the only disomic gene found to be significantly upregulated in the soleus muscles of Ts1Cje mice. Western blot analysis on three proteins of the myogenic regulatory factors (MRFs) family namely MyoD, Myf5 and Myg showed no significant difference in expression in both muscles. Following the targeted study, transcriptomic profiling of the soleus and EDL muscles of the Ts1Cje and wild-type disomic mice using microarray was performed. Results showed a total of 166 coding DEGs found in soleus muscles with 37 of them located on MMU16 and a total of 262 coding differentially expressed genes (DEGs) found in EDL muscles with 13 of them located on MMU16 (p-value ≤ 0.05, absolute fold change (abs FC) ≥ 1.5). Functional annotation clustering of these DEGs showed 5 significant functional clusters for soleus (signal transduction; development of reproductive system; nucleic acid biosynthesis; protein modification and metabolism and regulation of gene expression) and 3 significant functional clusters for EDL (neuron and cell development; protein modification and metabolic processes; and ion transport). Validation of nine selected genes which were found to be differentially expressed in both soleus muscles and EDL muscles was performed using RT-qPCR. The genes were Cdk13, Mansc1, Ifnar1, Ifnar2, Donson, Dyrk1a, Runx1, Sod1, and Tmem50b with the later 7 the trisomic genes. The analysis showed that all genes were upregulated in Ts1Cje soleus muscles by ≥ 1.5 fold while only Don, Ifnar2 and Tmem50bwere upregulated in Ts1Cje EDL muscles by ≥ 1.5 fold. Western blot analysis of two of the trisomic genes at the protein level showed a downregulation of Ifnar1 in Ts1Cje soleus muscles and downregulation of Ifnar2 in both soleus and EDL muscles of Ts1Cje mice as oppose to being upregulated in microarray and RT-qPCR analysis. Collectively, these findings showed an overexpression of the trisomic genes in Ts1Cje skeletal muscles, validating the hypothesis that the dysregulation of the genes caused by the triplicated region of MMU16 leads to muscle weakness in Ts1Cje. However, further investigation on the role of these genes and the protein expression levels may provide further insight on the underlying mechanism responsible for muscle weakness in Ts1Cje